History and Development of Islamic Banking Regulations in the National Legal System of Indonesia - Shandy Utama, Andrew (al-'adalah, 2018)
The economic crisis in 1998 caused a number of national banks to collapse. Strangely, such a great crisis turned out to have no effect on the syari’ah banking world. Even as the crisis passed, a number of new Shari'ah banks emerged, such as Bank Syariah Mandiri, Bank Permata Syariah, Bank Mega Syariah, Bank Rakyat Indonesia Syariah, Bank Syariah Bukopin, and so forth. This study examines the development of Islamic banking in Indonesia. The aim is to find out factors driving and inhibiting the growth of these banking institutions. This study uses normative legal research methods. The results shows that the Islamic banking institutions could grow and develop rapidly due to two factors: internal and external factors. On the internal side, the Shari'ah bank has a usury management system that makes it able to withstand the economic crisis; while from the external side it has to do with government support, especially after the issuance of Law Number 21 of 2008.